Carbon Market within the Framework of Environmental Protection and Management Policies in Indonesia - Kristianto (Postgraduate School of Universitas Brawijaya, 2024)
Since climate change poses a significant global risk, the Indonesian government has introduced numerous regulations in line with its National Determined Contribution (NDC) goals. Aligned with the objectives of the Paris Agreement, Indonesia recently initiated a carbon trading system anticipated to fulfill the nation's NDC. Researching the legal framework is crucial for the continuous improvement and implementation of Indonesia’s carbon market, given its novelty and the challenges that must be addressed. Addressing climate change through carbon trading is integral to Indonesia's environmental protection and management strategies, reflecting a deliberate endeavor towards sustainable development. Nonetheless, to realize zero emissions, comprehensive research on the Carbon Market is essential to ensure its alignment with Indonesia's Environmental Protection and Management Law and to bolster the Sustainable Development Goals. This research paper utilizes normative legal studies to explore carbon trading within the legal framework based on Environmental Law policies. Adopting a similar approach to developing Indonesia's Environmental Law since 1982, it is anticipated to bolster the successful implementation of a carbon market in Indonesia aimed at reducing the nation’s carbon emissions and fulfilling its Nationally Determined Contribution (NDC). Keywords: carbon market, environmental law, Indonesia perspective, sustainable development, SDG’s